Pengaruh Modal Kerja, Ukuran Perusahaan dan Leverage Operasi terhadap Profitabilitas pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Rasyid, Rosyeni; Rahmiati, Rahmiati; Youlandari, Tisya Pretty (Jurnal Kajian Manajemen Bisnis, 2014)
The purpose of this research is to determine 1) the effect of working capital to profitbility of food and beverage company listed in Indonesia Stock Exchange, 2) the effect of firm size to profitability of food and beverage company listed in Indonesia Stock Exchange 3) the effectof operating leverage to profitability of food and beverage company listed in Indonesia Stock Exchange. The research sampel are 16 food and beverage company listed in Indonesia Stock Exchange (IDX) around 2007-2012. This research used purposive sampling method. The statistical methods used in this research are multiple regressions. The results of this reseach indicate that: (1) working capital (WCT) have positive and significant effect to profitability of food and beverage company (2) firm size (TA) have negative and no significant effect to profitability of food and beverage company, and (3) the operating leverage have negative and significant effect to profitability of food and beverage company.